2009
DOI: 10.1259/dmfr/19195745
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution magnetic resonance imaging and diffusion tensor imaging of the porcine temporomandibular joint disc

Abstract: Objectives: Diffusion tensor imaging (DTI) is an MRI modality for characterizing the property, microstructural organization and function in tissues such as the brain and spinal cord. Prior to this investigation, DTI had not been adapted for studies of the temporomandibular joint (TMJ) disc. Objectives were to test the feasibility of DTI to evaluate the porcine TMJ disc and to use DTI to observe differences in magnitude of anisotropy of water diffusion between TMJ disc regions. Methods: Five adult pig TMJs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…4). Similar results were also found by DTI measurements of 3D water diffusion in porcine TMJ discs 24 . However, the fractional anisotropy of water diffusion (0.36–0.55) in the DTI study was higher than the fluorescein diffusion (0.13–0.30) in this study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…4). Similar results were also found by DTI measurements of 3D water diffusion in porcine TMJ discs 24 . However, the fractional anisotropy of water diffusion (0.36–0.55) in the DTI study was higher than the fluorescein diffusion (0.13–0.30) in this study.…”
Section: Discussionsupporting
confidence: 88%
“…, region dependent) 23 . A recent diffusion tensor imaging (DTI) study also showed the anisotropic and region-dependent behavior of water diffusion in porcine TMJ discs 24 .…”
Section: Introductionmentioning
confidence: 95%
“…16 Most recently, Benavides et al reported that there is a region-dependency of water diffusion in porcine TMJ disc using diffusion tensor MRI. 2 In the anteroposterior direction, the mean water diffusivity was higher in the anterior and posterior bands compared with the intermediate zone. In the mediolateral direction, the mean water diffusivity was higher in the medial and lateral aspects than in the center.…”
Section: Discussionmentioning
confidence: 90%
“…In the dental field a very promising novel approach is real-time imaging of TMJ movement by means of FLASH MRI [48]. Diffusion tensor imaging may in future provide another promising option for non-invasive diagnostics of microstructural soft tissue changes in the TMJ [49]. Apart from TMJ imaging, MRI has also been demonstrated to be useful for imaging of structures such as alveolar bone or teeth [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Another very modern concept seems to have great potential for TMJ imaging: diffusion tensor imaging (DTI). In an experimental study on pig cadavers Benavides et al [49] demonstrated that microstructural properties of the porcine TMJ disc as detected by proton diffusion could be useful for a non-invasive characterization of the disc.…”
Section: Applications In Dentistrymentioning
confidence: 99%